Strigolactones and Cytokinin Interaction in Buds in the Control of Rice Tillering - Zha, Manrong; Zhao, Yanhui; Wang, Yan; Chen, Bingxian; Tan, Zecheng (Frontiers in Plant Science, 2022)
Shoot branching is among the most crucial morphological traits in rice (Oryza sative L.), and is physiologically modulated by auxin, cytokinins (CK), and strigolactones (SLs) cumulatively in rice. A number of researches focused on the interplay of these three hormones in regulating rice tiller extension. The present study primarily aimed at the impact of different treatments, which were used to regulate rice tiller and axillary on node 2 at tillering stage as well as full heading stage, respectively. Transcription levels of several genes were quantified through qRT-PCR analysis, and the endogenous auxin and four types of CK contents were determined through LC-MS/MS. Both, nutrient deficiency and exogenous SL supply were found to be inhibiting rice tiller outgrowth with reducing CK contents in tiller buds. Furthermore, both exogenous SLs and endogenous SL-synthesis inhibitor supply could also affect the expression level of OsCKX genes but not of the OsIPT genes. Comparison of OsCKX genes expression pattern under exogenous SL and CK supply suggested that SLs induced OsCKXs expression was most likely via CK-induced independent pathway. These result combined with cytokinin-type-A RR genes expression in bud support a role for SLs regulating bud outgrowth through regulation of local CK levels. SL functioned antagonistically with CK in regulating the outgrowth of buds on node 2, by promoting the OsCKX genes expression in buds.